An analysis of the implementation of COVID-19 handling and control governments in Indonesia - ZA, Safrizal; Maimun, Maimun; Syahbandir, Mahdi; Syamsulrizal; Hasan, Efendi (Institute of Education and Social Research, 2024)
The novel coronavirus has caused 6.85 million human deaths worldwide. The World Health Organization (WHO) says the coronavirus is here to stay, despite the declining trend of cases, but serious efforts are needed from all elements of society to end this global health crisis. Indonesia is one of the countries that is very consistent in suppressing the spread of the virus, one of the breakthroughs made is activating local government tools for prevention and serious handling. The purpose of this paper is to provide an overview of the Coronavirus prevention and handling model carried out by local governments throughout Indonesia. The results of this study prove that as many as 38 provinces with 415 districts in Indonesia have not been able to maximally implement the coronavirus prevention and handling model following the framework formulated by the Indonesian Ministry of Health, this is due to many factors, including; the work culture of the state apparatus, weak middle-level management, as well as weak monitoring and evaluation issues.